Academic cost of student mobility: COVID-19 restrictions as a natural experiment - Luis Rumert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
The COVID-19 pandemic forced university students to transition to online learning due to mobility restrictions and campus closures. When in-person teaching resumed, many students had to commute or move closer to campus and adapt to a new learning and social environment. This paper examines how this mid-study return to campus impacted academic performance and whether all students had to bear the same costs. Using administrative student data from a public university in North Rhine-Westphalia, Germany and a difference-in-differences approach, the results show an overall significant but small decrease in passed credit points and the number of registered exams. The effects increase over time and reach a 14 percent decrease in passed credit points and a 13 percent decrease in registered exams after five semesters. Additionally, the overall dropout probability decreases by 33 percent. The estimated effects are heterogenous with respect to cohorts, sex, and migration background. Moreover, the cost of student mobility increases by distance.
Keywords: I23; R23; I38; 330; Student mobility; reopening of universities; academic performance; difference-in-differences